Comparative Study on Seismic Resistant Design Using Base Isolation System - ไทรงาม ภาณุมาศ; Hlaing, Hnin Hnin (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 28, 2023)
Earthquakes are the most destructive natural hazards throughout human history. Seismic-resistant design is important in areas of the world where earthquakes are common as it can help to reduce the risk of loss of life and property damage. To reduce the effects of earthquakes on buildings, a base isolation system is a type of seismic-resistant design to improve the seismic performance of the buildings. This study investigates and compares the seismic performance of the buildings with and without the base isolation system. A seven-storey RC building is used as a target numerical model. The high-damping rubber bearings with three different damping ratio values are used as the seismic isolation device. The isolators are placed at the base of all columns of the building to lengthen the period of vibration of the building. This affects the reduction of the base shear which induced by the earthquake. According to International guidelines, isolators are designed based on support reaction under only gravity load after performing static analysis to obtain unfactored column loadings. The response spectrum analysis is used in dynamic analysis. The displacement of the base isolation system is larger than that of the fixed base buildings even as having lower story accelerations, story drifts ratios, and story shears. The high-damping rubber bearings have a high damping coefficient which can dissipate a significant amount of energy during an earthquake, reducing the seismic forces and displacements on the structure.